The Effect of the Breast Care, Oxytocin Massage, and Marmet Technique (BOM) Method on Breast Milk Production - Yohana Sembiring; Diah Evawanna Anuhgera; Siti Choirul Dwi Astuti; Iskandar Markus Sembiring (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Breast milk is the optimal source of nutrition for infants; however, inadequate milk production remains a common problem among postpartum mothers, particularly during the early days after delivery. Objective: This study aimed to analyze the effect of the Breastcare, Oxytocin Massage, and Marmet Technique method on breast milk production in postpartum mothers. Method: This study used a quasi-experimental design with a post-test only control group approach. A total of 20 postpartum mothers were selected using purposive sampling and divided into an intervention group that received the Breastcare, Oxytocin Massage, and Marmet Technique method and a control group that received breastfeeding counseling. Data were collected using a questionnaire measuring indicators of infant adequacy, including urination frequency, defecation patterns, sleep duration, and weight changes, and were analyzed using the Mann–Whitney test. Results: The findings show that breast milk production in the intervention group is significantly higher than in the control group (p = 0.001), with a higher mean rank observed in the intervention group. The method enhances milk production through hormonal stimulation, mechanical stimulation, and psychological relaxation, which support the secretion of prolactin and oxytocin and facilitate milk ejection. Conclusion: The Breastcare, Oxytocin Massage, and Marmet Technique method is an effective non-pharmacological intervention that improves breast milk production and facilitates milk ejection in postpartum mothers, and it can be recommended to support exclusive breastfeeding.